Itihāsera Kālarātri - Śāhajāhāna, Mohāmmada (Dāudakāndi Thānā Āoẏāmī Līga], 1983)
Commemoration volume for Sheikh Mujibur Rahman, 1922-1975, former president of Bangladesh; comprises articles, poems, and reminiscences of his associates.